2002
DOI: 10.1002/1521-3773(20020104)41:1<124::aid-anie124>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Enantioselective Catalysts by Immunoassay

Abstract: More than 1000 yields and ee determinations are possible per day using an immunoassay. This highly efficient screening method is based on the remarkable binding specificity of antibodies. It has been employed in the development of straightforward procedures for the direct conversion of α‐keto acids into chiral α‐hydroxy acids, for which the enantioselective reduction of benzoyl formic acid to mandelic acid serves as a model reaction (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(55 citation statements)
references
References 51 publications
1
54
0
Order By: Relevance
“…This method is by far the most used for the preparation of magnetic nanoparticles useful in biotechnology applications such as for example detection. One promising approach for detecting minute traces of enantiomeric impurities utilizes stereoselective antibodies [12]. Recently, Tsourkas et al, have reported a novel homogeneous enantioselective immunosensor that utilizes magnetic relaxation switching as the detection element [13].…”
Section: Coprecipitationsupporting
confidence: 64%
“…This method is by far the most used for the preparation of magnetic nanoparticles useful in biotechnology applications such as for example detection. One promising approach for detecting minute traces of enantiomeric impurities utilizes stereoselective antibodies [12]. Recently, Tsourkas et al, have reported a novel homogeneous enantioselective immunosensor that utilizes magnetic relaxation switching as the detection element [13].…”
Section: Coprecipitationsupporting
confidence: 64%
“…Wagner and Mioskowski [31] used a similar idea to develop a high-throughput screening method for the enantioselective catalytic reduction of ketones. Using competitive enzyme immunoassays (EIA) [32], the yield as well as the enantiomeric excess of the reaction could be measured for "thousands" of catalysts per day.…”
Section: Biological Methodsmentioning
confidence: 99%
“…A chromophore may be installed into the substrate [13] or product [14] of the reaction under study. Alternatively, one can exploit chromophores inherent in proteins [15] or enzyme-associated reactions, [16] and use these sensors to report back on product formation and composition.…”
mentioning
confidence: 99%